IMPROVING SKILLS READING FAST AND STUDENT LEARNING THROUGH THE QUANTUM READING MODEL - Reny Romantiwi; Ika Mustika; Dida Firmansyah (JLER (Journal of Language Education Research), 2018)
Language is a medium to communicate in social life so it is with the Indonesian language which is the official language that its use has been widespread and involving various areas of life. The author formulates the problem as follows: 1. Are students' fast reading skills using the Quantum Reading model better than using a conventional approach? 2. Is the student's interest in learning using the Quantum Reading model more likely to increase than using a conventional approach? 3. Is there a correlation between student's learning interest and reading comprehension skills? Based on the formulation of this research problem aims to 1. Understanding students' reading comprehension skills learning using Quantum Reading model compared with learning using a confessional approach. 2. Analysis of student learning interest in learning by using the model of Quantum Reading compared with learning using a confessional approach. The author's hypothesis is 1. Fast reading skill learning using the Quantum Reading model is better than learning using conventional learning. 2. Interest in learning of students whose learning using Quantum Reading model is better than learning using conventional learning.